2015
DOI: 10.1063/1.4915606
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz magnetic and electric Mie resonances of an all-dielectric one-dimensional grating

Abstract: Resonantly enhanced Raman scattering in dielectric nanostructures has been recently proven to be an efficient tool for developing nanothermometry and experimental determination of their mode-composition. In this paper, we develop a rigorous analytical theory based on the Green's function approach to calculate the Raman emission from crystalline high-index dielectric nanoparticles. As an example, we consider silicon nanoparticles which have a strong Raman response due to active optical phonon modes. We relate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…It is interesting to note that the second TE resonance is a sharp dip with a narrower linewidth and a higher Q-factor. In addition, almost half of electric fields and magnetic loops are concentrated in the silicon pillars whereas the else parts disperse in the background slabs [8] . Therefore, the resonator is sensitive to the dielectric condition of surrounding media.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that the second TE resonance is a sharp dip with a narrower linewidth and a higher Q-factor. In addition, almost half of electric fields and magnetic loops are concentrated in the silicon pillars whereas the else parts disperse in the background slabs [8] . Therefore, the resonator is sensitive to the dielectric condition of surrounding media.…”
Section: Resultsmentioning
confidence: 99%
“…THz radiation has a fundamental relevance 28 in a variety of fields ranging from astronomy to biology and it is crucial for the development of information technologies, including sixth-generation (6G) communication and THz integrated circuits. This growth of important applications in diverse fields calls for the development of devices with new functionalities and all-dielectric metamaterials have emerged as a promising platform for highly efficient THz systems 29 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In this work we report on an experimental study of THz pulses propagation in the diffusive regime to investigate the effects and quantify the amount of disorder in FDM multilayer structures made of free-standing arrays of rectangular rods of dielectric polymeric material. Previous works on the same topic were focused on single grating: the angular dependence of the diffracted beams of a 3D printed single grating were compared to theoretical simulations 42 , and Mie resonances were characterized by using THz time-domain spectroscopy (THz-TDS) in a dielectric grating obtained by direct-laser-writing technique on a Si wafer and compared to finite-element simulations 29 . We also experimentally characterize the 3D printed photonic structures by measuring the transmittance of the multilayer stacking by THz-TDS.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the absorbers with narrower absorption bandwidth have better performance in the applications of thermal emitters and sensors 8,21 . Up to date, some ultra-narrowband absorbers have been proposed by manipulating electromagnetic resonance in metallic microstructures [22][23][24][25][26] .In recent years, it has been found that dielectric metamaterials (DMs) composed of dielectric microstructures can also be used to manipulate electromagnetic resonance [27][28][29][30][31][32] . Due to the unique advantage of the low loss, dielectric metamaterials provide an ideal resolution for narrowing the absorption bandwidth [33][34][35] .…”
mentioning
confidence: 99%
“…In recent years, it has been found that dielectric metamaterials (DMs) composed of dielectric microstructures can also be used to manipulate electromagnetic resonance [27][28][29][30][31][32] . Due to the unique advantage of the low loss, dielectric metamaterials provide an ideal resolution for narrowing the absorption bandwidth [33][34][35] .…”
mentioning
confidence: 99%